(untitled) (Research, Society and Development, 2025)
The present study aims to perform a literature review on the main irrigation systems and activation techniques used in endodontics, highlighting their properties, mechanisms of action, clinical efficacy and indications. The use of irrigating solutions with antimicrobial and organic matter dissolving properties are essential, especially in areas that are difficult to access, such as the apical region. Several substances and techniques have been developed to enhance irrigation. The combination of sodium hypochlorite (NaOCl) and EDTA is considered the most effective in disinfecting and removing the smear layer. Activation systems, such as XP-endo Finisher®, EasyClean®, EndoActivator®, PUI (passive ultrasonic irrigation), negative pressure irrigation (EndoVac®, RinsEndo®), and laser, have been shown to be superior to conventional syringe irrigation, promoting greater penetration and effectiveness of the irrigant. Passive ultrasonic irrigation stands out for its ability to remove debris in apical and lateral regions. EasyClean®, in turn, showed equivalent efficacy, especially when used in continuous rotation. EndoVac® stands out for safely guiding the irrigant to the apex, avoiding extrusion. Although each system has specific indications, there is no universally ideal protocol. The choice of method should consider the anatomy of the canal and the stage of treatment. It is concluded that the combination of effective irrigating solutions and appropriate activation systems is essential to optimize cleaning and clinical success of endodontic treatments.